The impact of disciplinarity on the cognitive leadership frames of academic deans in Jordan - Aieman Ahmad Al-Omari (International Journal of Education and Learning, 2020)
The purpose of this study is to address how academic deans at Jordanian Universities perceive their cognitive leadership frames (bureaucratic, collegial, political, and symbolic frames) based on their disciplines. One hundred thirty-four academic deans have completed the survey and used in this study, with a response rate of 93%. As for discipline, there were scientific 56 and 78 humanities disciplines. A questionnaire with 22 items grouped into four scales, one each for the bureaucratic, collegial, political, and symbolic frames. The results indicated that the bureaucratic leadership frame has a high level than all other cognitive leadership frames, followed by a political leadership frame with a high level, followed by a collegial leadership frame with a moderate level, and a symbolic leadership frame moderate level. T-test results revealed that the Bureaucratic leadership frame and political leadership frame had significant differences in favor of scientific discipline. In comparison, collegial and symbolic leadership frames had no significant differences. The study recommended that university leaders should support academic deans to enroll workshops and partake comprehensive training on cognitive leadership frames to help them realize their full potential in contributing and developing their colleges and universities.